2011
DOI: 10.4302/plp.2011.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of a 2x2 electro-optic Mach-Zehnder Interferometer optical switch with s-bend arms

Abstract: Abstract-In this paper, we present a 2×2 electro-optic switch based on a Mach-Zehnder interferometer (MZI) with tapered (s-bend) interferometric arms. All structures have been designed with a channel profile of titanium indiffused lithium niobate waveguides. The crosstalk analysis of the switch suggests that the crosstalk levels become worse (-12dB) when both interferometric arms of the structure are tapered. We have optimized the structure in order to reduce the overall switch losses (≤ 0.5dB) and to achieve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 5 publications
(8 reference statements)
1
12
0
Order By: Relevance
“…From the previous results, it is clear that extinction ratio and insertion loss are major drawbacks for titanium diffused lithium niobate switches under the previous parameters. Previous literature suggested that, these two drawbacks can be enhanced by controlling titanium strip thickness before diffusion [18]. This will be investigated in the following section.…”
Section: Simulation For Basic Ti:linbo 3 2×2 Switch Operating At 13µmmentioning
confidence: 99%
See 1 more Smart Citation
“…From the previous results, it is clear that extinction ratio and insertion loss are major drawbacks for titanium diffused lithium niobate switches under the previous parameters. Previous literature suggested that, these two drawbacks can be enhanced by controlling titanium strip thickness before diffusion [18]. This will be investigated in the following section.…”
Section: Simulation For Basic Ti:linbo 3 2×2 Switch Operating At 13µmmentioning
confidence: 99%
“…In this section, we are going to investigate the effect of titanium strip thickness on for titanium diffused lithium niobate switch using a sample of suggested range from 0.048 µm to 0.062 µm in [18]. Table 5 represents the results of studying important design parameters under the samples of suggested Ti strip thickness range.…”
Section: Exploring the Effect Of Titanium Strip Thickness On The Perfmentioning
confidence: 99%
“…9) has been monitored. The power imbalance at the output splitter can be obtained using following definitions (Singh et al 2012).…”
Section: Study and Analysis Of Some Factors Influencing The Performanmentioning
confidence: 99%
“…Due to variation of the refractive index, the phase difference arises, and depending upon the phase, signal shifts from one waveguide to another waveguide. LiNbO 3 based MZI is characterized by the attractive features of compact size, thermal stability (Wooten et al 2000), re-configurability (Jin et al 2014), integration potential (Wooten et al 2000), low latency and low power consumption (Singh et al 2012;Kumar Kumar et al 2015b). Due to which many researchers have shown their keen interest and implemented various combinational and sequential circuits using MZIs (Kumar et al , 2014a(Kumar et al , b, 2015aRaghuwanshi et al 2013Raghuwanshi et al , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, in this paper, authors have demonstrated the design for an optical counter based on electro-optic (EO) effect of LiNbO 3 based Mach-Zehnder interferometer (MZI). LiNbO 3 based MZI is characterized by the attractive features of compact size, thermal stability (Wooten et al 2000), re-configurability (Jin et al 2014), integration potential (Wooten et al 2000), low latency and low power consumption (Singh et al 2012;Kumar et al 2015b). Due to which many researchers have shown their keen interest and designed various combinational and sequential circuits using MZIs (Kumar et al , 2014a(Kumar et al , b, 2015aRaghuwanshi et al 2013Raghuwanshi et al , 2014.…”
Section: Introductionmentioning
confidence: 99%